Representation of Sovereign Power and Its Resistance in Wonka (2023): Barthes' Semiotics Analysis - Fitra Hanif; Fikri Arya Nurrachman; Muhammad Faisal Rahmadin (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This study explores the representation of power relations, particularly sovereign power and resistance, in the film "Wonka," directed by Paul King. Utilizing a descriptive-qualitative approach and applying Roland Barthes' semiotic theory of denotation and connotation, the research analyzes key scenes to reveal how power dynamics are depicted through violence, authority, and control. The narrative follows Willy Wonka's journey as he confronts the oppressive forces of a chocolate cartel, illustrating the complexities of power and the resilience of individuals who resist such dominance. The findings highlight the film's broader socio-political themes, emphasizing the transformative potential of resistance and the capacity of visual media to critique power structures. Ultimately, this study underscores the significance of film as a medium for social commentary and its role in envisioning alternative power dynamics, offering insights into the interplay of power, resistance, and storytelling in contemporary cinema.